Nature of delirium liberating act: essential action, evidence and awakeing - Barrientos Rastrojo, José (Estudios de Filosofía, 2011)
Most studies on delirium spend time discussing its conceptual portrayal, namely, its etiology, its basic elements and its explicit symptoms. This article analyzes its metaphysical grounds by means of zambranian thought. Furthermore, it studies the philosophical skeleton of this pathology exits. By this way, it is exposed a perspective whose focus is the nature of the delirium liberating act and not just specific strategies of healing it.